Photodegradation Pathways of Typical Phthalic Acid Esters Under UV, UV/TiO2, and UV-Vis/Bi2WO6 Systems - Wang, Chunying; Zeng, Ting; Gu, Chuantao; Zhu, Sipin; Zhang, Qingqing; Luo, Xianping (Frontiers in Chemistry, 2019)
Photolysis and photocatalysis of typical phthalic acid esters (dimethyl phthalate, DMP; diethyl phthalate, DEP; dibutyl phthalate, DBP) were carried out in UV, UV/TiO2 and UV-Vis/Bi2WO6 systems. All selected phthalic acid esters and the decomposition byproducts were detected in qualitative and quantitative analysis through HPLC and GC-MS. As the results of the photolysis and photodegradation, each system demonstrated different removal ability to DMP, DEP and DBP. UV/TiO2 system showed the strongest degradation ability on DMP and DEP, while UV-Vis/Bi2WO6 almost had no removal ability to DMP and DEP. However, all systems had strong degradation ability to DBP. On the other side, different systems resulted in various byproducts and degradation pathways of PAEs. The UV system mainly attacked the carbon branch, and produced o-hydroxybenzoates. There were no ring-opening byproducts were detected in the UV systems. In the photocatalytic process, the produced hydroxyl radicals not only attacked the carbon branch, but also attacked the benzene ring. Therefore, hydroxylated compounds and ring-opening byproducts were both detected by GC-MS in UV/TiO2 and UV-Vis/Bi2WO6 photocatalytic systems. However, there were fewer products due to the direct hole oxidation in UV-Vis/Bi2WO6 system compared with UV/TiO2 system which mainly reacted with pollutants by hydroxyl radicals.